Towards an Ethical Fashion Framework. (26th May 2016) - Haug, Anders; Busch, Jacob
Abstract: Definitions of ethical fashion have a strong focus on the responsibility of the providers and the consumers of unethical fashion items. This paper argues that such understandings of the problems and solutions ignore important aspects. To provide a clearer picture of the situation, this paper identifies the relevant actors and their mutual influences.